Assessment of anti-snake venom effects of Acalypha fruticosa leaves against Indian Saw-scaled viper by using envenomed Wistar albino rats - Ramaswamy, Malathi; Duraikannu, Sivakumar; Solaimuthu, Chandrasekar (International Journal of Scientific Research in Biological Sciences, 2019)
Indian saw-scaled viper are one of the highly venomous snake found in Indian subcontinent and its venom has a wide variety of toxic compounds and it can able to causing severe envenoming characterized by severe pharmacological effects. The traditional knowledge on the Acalypha fruticosa plant was clearly states that this plant was used against the venomous bites and stings. In best of our knowledge, there were no any scientific reports to justify the anti-snake venom potential of this plant. The main objective of the present research work was to evaluate the anti-snake venom activity of A. fruticosa against Indian saw-scaled viper venom using envenomed animal model. The effects of ethanolic leaves extract of A. fruticosa on hematological parameters of experimental rats, saw-scaled viper venom induced liver toxicity, renal toxicity and blood metabolites was analyzed in experimental rats. In the present study, the ethanolic leaves extract of A. fruticosa leaves was inhibited the venom induced changes in hematological parameters. The plant extract was effectively decreased the saw-scaled viper venom induced liver toxicity and renal toxicity in experimental rats. The observed results clearly states that the A. fruticosa leaves has potent snati-snake venom activity.